30.3: The Design Parameters for a Curved Barrier‐type Auto‐stereoscopic Display. Issue 1 (June 2015) - Lin, Wei‐Chieh; Cheng, Yun‐Ting; Huang, Kuo‐Chung; Lin, Hoang Yan
Abstract : In this paper, we verify the design method from planar to flexible barrier‐type auto‐stereoscopic displays used in mobile device. According to the design method, the curvature radius R of display, and the aperture ratios aB and aD of barrier and pixel are the only parameters to change the viewing zone. For R larger or smaller than a threshold value, aB and aD have different effects on 3D performance.